Clicks and mortar : passion-driven growth in an internet-driven world - Pottruck, David S. (Jossey-Bass San FranciscoUS, 2000)
Provides 3 guidelines for the way forward in the current Internet-transformed business scenario - firstly: building and sustaining of a passionate corporate culture based on strong values; secondly: leadership that models integrity both in private and corporate life, that communicates, and generates innovation; and thirdly: modifying management practices.